(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
In India, the production of steel slag is about 12 million tons in the steel industries and we can use in our concrete as a waste material. Concrete is most commonly and widely used building material used in all around the world. Concrete is the mixture of cement, sand, aggregates (fine and coarse), and water. The utilization of concrete is continuously increasing due to which there is a great effect on natural resources. There are many numbers of by products (like, steel slag, silica fume, fly ash, etc.) that are produced during the production or the manufacturing of material like steel, silicon metal, etc. In the present study effect of silica fume on steel slag concrete has been carried out on M25 grade of concrete by varying percentage of steel slag i.e. 45%, 50% and 55% and constant value of silica fume i.e. 10%. From the study it has been observed that the compressive strength decreases while increases the percentages of steel slag. Therefore, up to 45% replacement of steel slag with the fine aggregates and 10% replacement of silica fume with cement give best result and after that the strength will decreases.